Propuesta de un plan estratégico de comunicación corporativa para posicionar Aerolíneas Galápagos "AEROGAL" como aerolínea comercial de bandera ecuatoriana - Berríos Montalvo, Manuel Andrés (2010)
At present, Ecuador does not have a flag commercial airline recognized to an international level, so that in this manner the country could be represented by a dependable, secure airline and, above all, competitive to a national and international level. The last airline that represented de country was Ecuatoriana de Aviación, being owned with state capital, the company found itself wrapped in budget problems and of competitiveness to an international level and, little by little it started loosing prestige until it disappeared. Since the 80s, Ecuador has been left without a commercial airline of flag that represents and be the prop of the aeronautical market of the country. This event marks a great lost in the country in the sectors: economic, tourism and social; at the same time given origin, after many years of wait, a great opportunity for a group of people with initiative and Ecuadorian capital manage to create the first flag airline. AEROGAL initiates operations in the year nineteen eighty- five to perform air transport for passengers and cargo on the mainland of Ecuador and the Galapagos Archipelago. Currently, AEROGAL is affected by the presidential decree regarding the fuel subsidy for possessing third generation aircraft adapted to a forth-generation, being used for an average of twenty years, which represent a higher cost on fuel…